Validitas Aplikasi MyJumpLab dalam Mengukur Tinggi Lompatan Vertikal pada Atlet Bola Voli Putra - Khairil Anwar; Suharjana; Widyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to compare the results of vertical jump height measurements between the conventional Vertical Jump Test method and the MyJumpLab application. The study employed a quantitative approach with a comparative design. The research sample consisted of 30 male volleyball athletes from Universitas Negeri Makassar who were selected using purposive sampling. Data were collected through three jump trials and then analyzed using descriptive statistics, the Shapiro–Wilk normality test, a paired sample t-test, and Pearson correlation analysis with the assistance of SPSS software. The results showed a significant difference between the two measurement methods (p < 0.05), with the mean measurement using MyJumpLab being slightly higher (63.50 cm) than that of the conventional method (62.13 cm). Nevertheless, the two methods demonstrated a very strong relationship, as indicated by a correlation coefficient of r = 0.984. This study concludes that the MyJumpLab application can be used as a valid, practical, and efficient alternative tool for measuring vertical jump height. Keywords: MyJumpLab, Vertical Jump Height Measurement, Vertical Jump Test.